Pengeluaran out of pocket rumah tangga untuk upaya pencegahan kesehatan anak: analisis berbasis two part model dan Tobit - Marlinda Marlinda; Vetty Yulianty Permanasari (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Out-of-pocket household expenditure for child health prevention services: two-part and tobit modelPurposeTo find out socio-economic determinants and the amount of out-of-pocket (OOP) for household expenditure in health prevention for children.MethodsThis study compared two approaches from several alternative assumptions including the two-part model and Tobit, which can be used when variable analysis has a problem selection. The dependent variable was household expenditure for children health prevention services in Indonesia, where the probability of dependent variable was affected by latent variables.ResultsThe two-part model and Tobit estimate that rural areas in NTT province can reduce out-of-pocket preventive health expenditures for children three times lower than the rural provinces of Papua. The higher the education of the head of the household, the greater of the possibility of preventive out-of-pocket child health is. Distribution of poverty rates based on quintiles provides a regressive picture of the poorest households based on expenditure per capita. ConclusionThis study is expected to be a comprehensive policy recommendation to suppress out-of-pocket preventive health expenditures for children. Thus, the distribution of health services is a priority for vulnerable groups (children) and the poor.